Physiological and metabolic responses to exercise on treadmill, elliptical trainer, and stepper: Practical implications for training - Bosch, A. N.; Flanagan, K. C.; Eken, M. M.; Withers, A.; Burger, J.; Lamberts, R. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Elliptical trainers and steppers are proposed as useful exercise modalities in the rehabilitation of injured runners due to the reduced stress on muscles and joints when compared to running. This study compared the physiological responses to submaximal running (treadmill) with exercise on the elliptical trainer and stepper devices at three submaximal but identical workloads. Authors had 18 trained runners (male/female: N = 9/9, age: mean ± SD = 23 ± 3 years) complete randomized maximal oxygen consumption tests on all three modalities. Submaximal tests of 3 min were performed at 60%, 70%, and 80% of peak workload individually established for each modality. Breath-by-breath oxygen consumption, heart rate, fuel utilization, and energy expenditure were determined. The value of maximal oxygen consumption was not different between treadmill, elliptical, and stepper (49.3 ± 5.3, 48.0 ± 6.6, and 46.7 ± 6.2 ml·min-1·kg-1, respectively). Both physiological measures (oxygen consumption and heart rate) as well as carbohydrate and fat oxidation differed significantly between the different exercise intensities (60%, 70%, and 80%) but did not differ between the treadmill, elliptical trainer, and stepper. Therefore, the elliptical trainer and stepper are suitable substitutes for running during periods when a reduced running load is required, such as during rehabilitation from running-induced injury.